2, 2′‐Azodi(2‐methylbutyronitrile) (AMBN) Promoted Alkenylation of Cyclic Ethers via Radical Addition to β‐Nitrostyrenes. Issue 13 (4th April 2022) - Shan, Xiaojie; Gao, Pan; Zhang, Shuwei; Jia, Xiaodong; Yuan, Yu
Abstract: It is reported the alkenylation of cyclic ethers via radical addition to β‐nitrostyrenes in the presence of AMBN without any other additives under mild conditions. A wide range of β‐nitrostyrenes and various ethers are tested in this reaction, most cases are happed smoothly with excellent to good yields. Cyclohexane also could be reacted under the conditions with moderate yield. According to the control experiments, the reaction mechanism was proposed. It is found that AMBN could induce to hydrogen abstraction from sp 3 carbon under oxygen atmosphere. This reaction system possesses the advantages of very high reactivity, stability, and convenient preparation method. Especially, it is very useful in the pharmacy industry due to the metal‐free and easy treatment conditions. Abstract : AMBN promoted alkenylation of cyclic ethers via radical addition to β‐nitrostyrenes under air or oxygen atmosphere with excellent to good yields. Linear ether and cyclohexane also could be reacted under the conditions with moderate yield. The reaction underwent the radical addition and denitro‐elimination mechanism. In addition, this reaction provides a new method to cleave relatively strong sp 3 C−H bond through the azo initiator directly.